Tackling the declining uptake of childhood vaccinations. Issue 5 (17th May 2019) - Dowden, Angela
Abstract : There has been a recent fall off in immunisation rates in England, and in 2017–18, coverage declined again in nine of the 12 routine vaccinations in preschool children. This article examines the reasons why, and looks at ways to combat the decline.